Association between stress and breast cancer in women: a meta-analysis Associação entre estresse e câncer de mama feminino: metanálise - Míria Conceição Lavinas Santos; Bernardo Lessa Horta; João Joaquim Freitas do Amaral; Paula Frassinetti Castelo Branco Camurça Fernandes; Cristina Maria Galvão; Ana Fátima Carvalho Fernandes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
The objective of the current meta-analysis was to verify the association between stressful life events and primary breast cancer incidence in women. A total of 618 studies from 1982-2007 were found in the PubMed, LILACS, and Cochrane Library databases. Methodological quality was evaluated according to the Downs & Black criteria. Eight studies were selected (six case-controls and two cohorts). The studies were grouped in three analyses, two of which based on the categories widowhood and divorce and the other based on self-rated intensity and frequency of stressful events. Relative risks were: widowhood 1.04 (95%CI: 0.75-1.44; p = 0.800); divorce 1.03 (95%: 0.72-1.48; p = 0.850); and intensity/frequency of stress 1.73 (95%CI: 0.98-3.05; p = 0.059). We conclude that stressful life events as a whole are not associated with risk of breast cancer in women. However, it is not possible to rule out high-intensity stress as a risk factor for breast cancer. O objetivo da presente metanálise foi verificar a associação de eventos de vida produtores de estresse com a incidência primária do câncer de mama entre as mulheres. Foram encontrados 618 estudos nas bases PubMed, LILACS e Biblioteca Cochrane Library, no período de 1982-2007. A qualidade metodológica foi avaliada pelos critérios de Downs & Black. Foram selecionados oito estudos, sendo seis caso-controle e dois de coorte. Os estudos foram agrupados em três análises, duas em virtude das categorias viuvez e divórcio, e uma considerando a intensidade autopercebida e freqüência de eventos. O risco relativo em relação à viuvez foi 1,04 (IC95%: 0,75-1,44; p = 0,800); ao divórcio foi 1,03 (IC95%: 0,72-1,48; p = 0,850), e em relação ao grau intensidade/freqüência de estresse foi 1,73 (IC95%: 0,98-3,05; p = 0,059). Concluímos que os eventos de vida produtores de estresse não têm associação de risco com câncer de mama feminino. O estresse de alta intensidade não permite eliminar a possibilidade de associação de risco para o câncer de mama.